2023
DOI: 10.1002/eji.202250270
|View full text |Cite
|
Sign up to set email alerts
|

Zfp362 potentiates murine colonic inflammation by constraining Treg cell function rather than promoting Th17 cell differentiation

Abstract: Mucosal barrier integrity and pathogen clearance is a complex process influenced by both Th17 and Treg cells. Previously, we had described the DNA methylation profile of Th17 cells and identified Zinc finger protein (Zfp)362 to be uniquely demethylated. Here, we generated Zfp362−/− mice to unravel the role of Zfp362 for Th17 cell biology. Zfp362−/− mice appeared clinically normal, showed no phenotypic alterations in the T‐cell compartment, and upon colonization with segmented filamentous bacteria, no effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…An interesting example of this is a recent study using a colitis model induced by transferring naïve CD4 + T cells into Rag2 -/- mice. These authors found that the transfer of naïve T cells deficient in the Zinc finger protein (Zfp)362 displayed a less severe colitis, which was associated with a reduction of Treg function rather than a higher promotion of Th17 differentiation 43 .…”
Section: Discussionmentioning
confidence: 99%
“…An interesting example of this is a recent study using a colitis model induced by transferring naïve CD4 + T cells into Rag2 -/- mice. These authors found that the transfer of naïve T cells deficient in the Zinc finger protein (Zfp)362 displayed a less severe colitis, which was associated with a reduction of Treg function rather than a higher promotion of Th17 differentiation 43 .…”
Section: Discussionmentioning
confidence: 99%
“…While ZFP362 expression is increased in Th17 and can interact with RORγT to promote Th17 differentiation [ 172 ], recent investigations have unveiled its regulatory role in IL-17-producing Treg differentiation. Notably, the level of IL-17-producing Tregs in the mesenteric lymph nodes of Zfp362 −/− mice surpasses that in wild-type mice [ 173 ]. Nevertheless, further exploration is warranted to fully elucidate the mechanisms by which ZFP362 regulates IL-17-producing Treg differentiation.…”
Section: Introductionmentioning
confidence: 99%